Autophagy in patients with lupus nephritis and its effect on podocyte related protein expression - LI Zhang-hong; ZHANG Rui-rui; LUO Qiu-ju (Linchuang shenzangbing zazhi)
Objective To investigate the autophagy in patients with lupus nephritis(LN)and its effect on podocyte related protein expression.Methods A total of 69 LN patients(LN group),including 50 cases of systemic lupus erythematosus(SLE group)and 50 patients with nephrectomy(control group)in our hospital from May 2017 to May 2019,were enrolled.Various indexes were compared among groups,including number of autophagosomes in the renal podocytes,the expression of autophagy-related proteins,microtubule-associated protein light chain 3(LC3),Beclin1,podocyte-associated proteins,Nephrin and Podocin.The renal podocytes were isolated from patients with lupus nephritis,and were divided into autophagy inhibition group and autophagy induction group.100 nmol/L 3-methyladenine(3-MA)was added for the autophagy inhibition group,and 100 nmol/L rapamycin(RAPA)was added for the autophagy induction group.The number of autophagosomes in the podocytes and the expression of LC3,Beclin-1,Podocin and Nephrin proteins were compared between groups.Results The number of autophagosomes in the podocytes and the expression of LC3,Beclin-1,Podocin and Nephrin proteins in the LN and SLE groups were significantly higher than those in the control group(P<0.05).The number of autophagosomes in the podocytes and the expression of LC3,Beclin-1,Podocin and Nephrin proteins in the SLE group were significantly higher than those in the LV group(P<0.05).followed by normal control group and autophagy inhibition group(P<0.05).The number of autophagosomes in the podocytes and the expression of LC3,Beclin-1,Podocin and Nephrin proteins in the autophagy induction group were significantly higher than those in the control and autophagy inhibition groups(P<0.05).The number of autophagosomes in the podocytes and the expression of LC3,Beclin-1,Podocin and Nephrin proteins in the control group were significantly higher than those in the autophagy inhibition group(P<0.05).Conclusions The level of autophagy in patients with lupus nephritis is elevated.The increase of autophagy level may reduce podocyte injury and inhibit the progression of lupus nephritis by up-regulating Podocin and Nephrin levels.